2018
DOI: 10.1038/s41598-018-29936-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between women’s perceived ideal gestational weight gain during pregnancy and pregnancy outcomes

Abstract: We aimed to clarify which beliefs motivate women to control their weight during pregnancy and how such values influence pregnancy outcomes. Using a questionnaire administered during mid- to late- pregnancy in a hospital-based prospective cohort study, we explored women’s perceived ideal GWG and their reasons for having this ideal. Using multivariate regression, we evaluated the association between women’s perceived ideal GWG and pregnancy outcomes. Among 1,691 normal and underweight women, the most common reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…A total of 7122 women who gave birth in those years in our hospital came from different regions in Slovakia and are working and living in the Bratislava agglomeration. In the observed period, although the women with overweight and obesity in our sample belonged to a lower limit of the obesity prevalence in pregnancy in the EU, based on our results, we can conclude that not only obesity with BMI ≥ 30.0 but also overweight with BMI between 25.0 and 29.9 is a high-risk factor for the occurrence of pathological conditions in pregnancy, such as preeclampsia, GDM, gestational hypertension, and IUGR [37,38]. Liu et al [39] showed that compared to antenatal weight gain within the IOM recommendations, excessive weight gain increased the incidence of cesarean section, preeclampsia, and infant macrosomia and reduced the incidence of GDM, while inadequate antenatal weight gain increased the incidence of GDM and low birth weight.…”
Section: Discussionmentioning
confidence: 58%
“…A total of 7122 women who gave birth in those years in our hospital came from different regions in Slovakia and are working and living in the Bratislava agglomeration. In the observed period, although the women with overweight and obesity in our sample belonged to a lower limit of the obesity prevalence in pregnancy in the EU, based on our results, we can conclude that not only obesity with BMI ≥ 30.0 but also overweight with BMI between 25.0 and 29.9 is a high-risk factor for the occurrence of pathological conditions in pregnancy, such as preeclampsia, GDM, gestational hypertension, and IUGR [37,38]. Liu et al [39] showed that compared to antenatal weight gain within the IOM recommendations, excessive weight gain increased the incidence of cesarean section, preeclampsia, and infant macrosomia and reduced the incidence of GDM, while inadequate antenatal weight gain increased the incidence of GDM and low birth weight.…”
Section: Discussionmentioning
confidence: 58%
“…A total of 7,122 women who gave birth in those years in our hospital came from different regions in Slovakia and are working and living in the Bratislava agglomeration. In the observed period, although the women with overweight and obesity in our sample belonged to a lower limit of the obesity prevalence in pregnancy in the EU, based on our results, we can conclude that not only obesity with BMI ≥ 30.0 but also overweight with BMI between 25.0 and 29.9 is a high-risk factor for the occurrence of pathological conditions in pregnancy, such as preeclampsia, GDM, gestational hypertension, and IUGR [37][38]. Liu et al [39] showed that compared with antenatal weight gain within the IOM recommendations, excessive weight gain increased the incidence of cesarean section, preeclampsia, and infant macrosomia and reduced the incidence of GDM, while inadequate antenatal weight gain increased the incidence of GDM and low birth weight.…”
Section: Discussionmentioning
confidence: 46%
“…This can be partly explained by applying WHO percentiles for BMI rather than ethnic-specific percentiles [3]. Body image in young women is suspected to contribute to the high prevalence of pre-pregnancy underweight and low gestational weight gain in Japan [13,20]. In our study, chronic diseases did not contribute to prepregnancy underweight.…”
Section: Discussionmentioning
confidence: 55%
“…Age and body weight and constitute main determinants of body image in women. Particularly in Japan, weight control among young women is discussed to contribute to the high prevalence of pre-pregnancy underweight [13,20]. Therefore, age may be an indirectly potentially modifiable risk factor by counselling young women.…”
Section: Discussionmentioning
confidence: 99%